2020
DOI: 10.1088/2053-1591/ab692b
|View full text |Cite
|
Sign up to set email alerts
|

Batch to batch variation study for biodiesel production by hydrothermal carbon catalyst: preparation, characterization and its application

Abstract: In the present study, the esterification of oleic acid with methanol was studied in batch to batch method over hydrothermal carbon catalyst (HTCC) from Ziziphus Mauritiana L.. The synthesized catalyst was characterized by FT-IR, XRD, XPS, SEM, and BET analysis. The surface area and acid density of prepared HTCC were found to be 15.97 m 2 g −1 and 2.53 mmol g −1 , respectively. Statistical analysis was performed by using ANOVA, mean, standard deviation and variance method. Statistically there is no significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…The efficiency of the carbon catalyst was 91%. The most significant advantage of such a catalyst is the possibility of its recovery and reuse [108].…”
Section: Comparative Analysis Of Hydrochar's Chemical and Physical Pr...mentioning
confidence: 99%
“…The efficiency of the carbon catalyst was 91%. The most significant advantage of such a catalyst is the possibility of its recovery and reuse [108].…”
Section: Comparative Analysis Of Hydrochar's Chemical and Physical Pr...mentioning
confidence: 99%
“…The resultant mixture is sonicated for 30-min using an ultrasonic sonicator to sonicate the suspension. After that, the solution was filtered, and the filtrated solution was titrated with an aqueous solution of 0.02 M NaOH solution using a phenolphthalein indicator 41 , 42 . Each titration result has been triplicated and their concordant value is noted.…”
Section: Methodsmentioning
confidence: 99%
“…Catalyst name N% C% S% H% Total acid density (mmol/g) www.nature.com/scientificreports/ phenolphthalein indicator 41,42 . Each titration result has been triplicated and their concordant value is noted.…”
Section: Si Nomentioning
confidence: 99%
“…The experiments showed that the maximum yield of biodiesel (60%) was obtained using the catalyst treated with 4-aminobenzenesulfonic acid, then the catalyst treated with phosphoric acid, sulfuric acid, combined sulfuric with nitric acid, sodium sulfide, and unaltered catalyst showed 43, 40, 24, 5 and 2% yields of biodiesel, respectively. 98 Carbonized black soldier fly larvae shells functionalized with p-toluene sulfonic acid gave 93.2% conversion of oleic acid. 107…”
Section: Influence Of the Sulfonating Agentmentioning
confidence: 99%